Preliminary insight into parental contributions to Japanese eel (Anguilla japonica) preleptocephali spawned on different nights. Issue 6 (29th September 2022) - Takeuchi, Aya; Sawayama, Eitaro; Kuroki, Mari; Miller, Michael J.; Watanabe, Shun; Tsukamoto, Katsumi
Abstract: Parentage sibship‐inference analyses were conducted using mtDNA sequencing and six microsatellite genotypes of 182 Japanese eel preleptocephali that were collected from one net‐tow near the West Mariana Ridge in May 2014. At least 328 parents were involved in producing the 182 preleptocephali, and several parents may have spawned a few times during 3 days of a spawning period. Half‐sibs suggested that a few parents mated with 1–3 partners, indicating that the Japanese eel can form spawning aggregations in which several parents mate with each other in the ocean.